Pure tone audiometry: recommended procedure - Ali, Akmaliza; Cheu Lih, Aw; Foong Yen, Chong; Selamat, Ellin Fariza; Lamri, Marina L. Alisaputri @ Marina; Omar, Marniza; Zakaria, Mohd. Normani; Abdul Wahab, Noor Alaudin; Abdullah, Nurul Ain; Bani, Nurul Huda; Rahmat, Sarah; Che Hussin, Siti Suriani; et al. (Malaysian National Society of Audiologists (MANSA), 2023)
This document was developed by the Working Group on Pure Tone Threshold Audiometry for adults under the office of the Malaysian National Society of Audiologists (MANSA). It presents recommended procedures of pure tone audiometry (PTA) testing based on existing evidence and research findings, as well as a consensus of recommendations found in the American Speech-Language-Hearing Association (2005) and the British Society of Audiology (2018). The intention is not to mandate a single way of accomplishing a clinical process, but to suggest standard procedures that in the final analysis should benefit the persons we serve. Although care has been taken in preparing this document, MANSA does not and cannot guarantee its interpretation and application. MANSA cannot be held responsible for any errors or omissions, and MANSA accepts no liability whatsoever for any loss or damage that may arise. The purpose of this document is to describe standard procedures and recommendations for effective PTA in most audiological settings. This document is not intended to provide guidance on specific circumstances or the interpretation of results. The audiologist carrying out the test must use professional judgment when deciding on the particular approach to be used with each person being tested, given the specific circumstances and the purposes of the test.